2012
DOI: 10.1155/2012/462121
|View full text |Cite
|
Sign up to set email alerts
|

“Keeping the Boogie Man Away”: Medication Self-Management among Women Receiving Anastrozole Therapy

Abstract: The oral hormonal agent anastrozole improves clinical outcomes for women with breast cancer, but women have difficulty taking it for the five-year course. The unique medication-taking experiences related to self-management of anastrozole therapy for women with early stage breast cancer are not known. Our purpose was to describe the medication-taking experiences for postmenopausal women with early stage breast cancer who were prescribed a course of anastrozole therapy. Twelve women aged 58 to 67 years, midway t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…Other scientists have measured severity of side effects (e.g., severe, moderate, mild, none) (Kahn et al, 2007) or number of side effects (Lash et al, 2006), but we were unable to find specific reports regarding weight concerns and nonadherence for women with breast cancer taking oral hormonal therapy. Our quantitative findings are somewhat consistent with the qualitative analysis of medication-taking for a subset of 12 women who participated in The Aim Study (Wickersham et al, 2012). They provided rich description of their side effects of therapy, which included hot flashes, arthralgias, fatigue, sleep disturbances, and memory problems.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Other scientists have measured severity of side effects (e.g., severe, moderate, mild, none) (Kahn et al, 2007) or number of side effects (Lash et al, 2006), but we were unable to find specific reports regarding weight concerns and nonadherence for women with breast cancer taking oral hormonal therapy. Our quantitative findings are somewhat consistent with the qualitative analysis of medication-taking for a subset of 12 women who participated in The Aim Study (Wickersham et al, 2012). They provided rich description of their side effects of therapy, which included hot flashes, arthralgias, fatigue, sleep disturbances, and memory problems.…”
Section: Discussionsupporting
confidence: 85%
“…Despite severity of their symptoms, most (11 of 12 participants, 91.67%) indicated that their side effects would not stop them from taking their anastrozole. The sentiments expressed by the women in our qualitative study (Wickersham et al, 2012) were consistent with the findings of the present secondary analysis; however, only two of the women in the qualitative analysis mentioned weight gain or weight loss in their descriptions of their medication-taking experiences with anastrozole. It is possible that women who had weight concerns had discontinued therapy with anastrozole before the interviews or attributed weight concerns to another process, such as aging.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The few studies on medication management by patients and family caregivers were conducted in a wide variety of clinical populations, including caregivers of patients receiving hospice services (19,22), breast cancer patients treated with oral chemotherapy (21), and frail older adults receiving home healthcare services (23,24). Medication regimens differ significantly across these populations and present unique challenges.…”
Section: Introductionmentioning
confidence: 99%